2019
DOI: 10.1111/joor.12760
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of the relationships between rhythmic masticatory muscle activities and limb movements in patients with sleep bruxism

Abstract: Summary Background Most rhythmic masticatory muscle activities (RMMAs) have been shown to be accompanied with limb movements (LMs) in sleep bruxism (SB) patients during sleep. Objectives To compare the relationships between RMMAs and LMs in SB patients and normal subjects. Methods Polysomnographic recordings were performed on eight SB patients and nine normal subjects and the frequencies and durations of RMMAs as well as LMs were determined. Linear regression and correlation analysis were performed to study th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 52 publications
(136 reference statements)
1
7
0
Order By: Relevance
“…Indeed, previous study reported that a much lower percentage of RMMAs could be evoked by peripheral stimulation in normal subjects than in SB patients although a similar percentage of transient cortical arousals could be evoked in both normal subjects and SB patients which suggests stronger and longer peripheral stimulation is needed to evoke occurrence of RMMAs in the normal subjects (eg AW) so longer cortical arousals (eg AW) would be more likely to occur and the resulting cortical excitation would be more likely to spread to more areas of the CNS, which might include the part controls LMs. This is supported by our recent findings that there was a lower frequency of RMMAs and a higher percentage of RMMAs accompanied by LMs in the normal subjects than in the SB patients and that there was a higher proportion of RMMAs with a companion of LMs associated with AW in the normal subjects than in the SB patients. Second, the parameters of HR increases associated with mixed RMMAs, but not with phasic and tonic RMMAs, in the SB patients were significantly different from those in the controls, which may be due to a lower (Wilcoxon rank‐sum test, P = .013) proportion of mixed RMMAs associated with AW and a significantly higher ( P < .05 for both) proportion of mixed RMMAs associated with mAR and NA in the SB patients than those in the controls, and no significant difference ( P > .05) in the phasic and tonic RMMAs associated with AW between SB patients and controls.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Indeed, previous study reported that a much lower percentage of RMMAs could be evoked by peripheral stimulation in normal subjects than in SB patients although a similar percentage of transient cortical arousals could be evoked in both normal subjects and SB patients which suggests stronger and longer peripheral stimulation is needed to evoke occurrence of RMMAs in the normal subjects (eg AW) so longer cortical arousals (eg AW) would be more likely to occur and the resulting cortical excitation would be more likely to spread to more areas of the CNS, which might include the part controls LMs. This is supported by our recent findings that there was a lower frequency of RMMAs and a higher percentage of RMMAs accompanied by LMs in the normal subjects than in the SB patients and that there was a higher proportion of RMMAs with a companion of LMs associated with AW in the normal subjects than in the SB patients. Second, the parameters of HR increases associated with mixed RMMAs, but not with phasic and tonic RMMAs, in the SB patients were significantly different from those in the controls, which may be due to a lower (Wilcoxon rank‐sum test, P = .013) proportion of mixed RMMAs associated with AW and a significantly higher ( P < .05 for both) proportion of mixed RMMAs associated with mAR and NA in the SB patients than those in the controls, and no significant difference ( P > .05) in the phasic and tonic RMMAs associated with AW between SB patients and controls.…”
Section: Discussionsupporting
confidence: 85%
“…The data from the polysomnographic recordings in the second night were used for further confirmation of SB and data analysis described below. Polysomnographic recordings of EEG (F3‐A2, F4‐A1, C3‐A2, C4‐A1, O1‐A2 and O2‐A1), electrocardiographic (ECG) and electrooculographic (EOG) activities as well as thoracic and abdominal respiration, nasal air flow, body posture and capillary oxygen saturation (SpO2) in index finger or thumb were performed . In addition, EMG activities from mylohyoid, bilateral masseter and limb muscles (bilateral gastrocnemius and tibialis anterior muscle, and bilateral flexor and extensor carpi radialis) were also recorded.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, in the SB group, the jaw motor system generating rhythmic activity may be more responsive to arousals [39]. Furthermore, previous findings showed that RMMA with limb and bodily movements was more closely related to higher cardiac and cortical activities [21,36,42]. Therefore, the close temporal relationship between oromotor and bodily movements may be mediated by a higher hierarchy of arousals that increases the excitability of multiple motor systems, such as at the trigeminal and spinal levels [6,7,10].…”
Section: Discussionmentioning
confidence: 95%
“…It is worth noting that phasic bruxism is the most common SB subtype [51,52]. Tonic bruxism episodes are the rarest; however, in healthy subjects, tonic bruxism is more common [53]. Increased severity of phasic bruxism was observed in hypertensives, while the tonic activity was similar in hypertensives and normotensives [54].…”
Section: Discussionmentioning
confidence: 97%